Clinical characteristics including cardiovascular and metabolic risk factors in adolescents with psoriasis. (19th February 2020) - Blegvad, C.; Nybo Andersen, A.‐M.; Groot, J.; Zachariae, C.; Barker, J.; Skov, L.
Abstract: Background: Clinical studies on psoriasis in adolescents have mainly been performed in patients with severe psoriasis. Population‐based studies of clinical characteristics and risk factors for later cardiovascular and metabolic disease in children and adolescents are lacking. Objectives: To examine the clinical characteristics of adolescents with psoriasis nested in a general population cohort. Furthermore, to investigate cardiovascular and metabolic risk factors in the adolescents with psoriasis compared to parentally predisposed and non‐predisposed adolescents without psoriasis from the same birth cohort. Methods: We identified adolescents with and without psoriasis using a nationwide general population birth cohort in Denmark. A clinical examination included skin inspection and scoring of psoriasis severity, completion of a questionnaire on psoriasis and comorbidities, physical measurements, and blood sampling. Participants also completed self‐administered questionnaires on quality of life and mental health. Results: We included 81 adolescents with psoriasis and 234 controls (110 with genetic predisposition for psoriasis and 124 without predisposition). Median age was 15.6 (13.5–18.5) years, and in those with active psoriasis, median Psoriasis Area and Severity Index score was 1.2 (0.1–11.4). The scalp was the most common site of psoriasis, both at debut and at time of examination. Diaper rash in infancy was more frequent in the psoriasis group. No significant differences regarding quality of life, anxiety and depression were found. More adolescents with psoriasis were obese (8.6% vs. 1.7%, P = 0.008), and physical measures of abdominal obesity were also significantly higher. HbA1c was significantly higher (31.55 vs. 30.81 mmol/mol, P = 0.048), while no differences were found for blood pressure, lipids or high‐sensitivity C‐reactive protein. In a subgroup analysis, this was evident in the non‐predisposed psoriasis‐free controls only. Conclusions: Overall, adolescents with psoriasis from this general population had mild disease. Still, early markers of cardiovascular and metabolic disease were elevated. Abstract : Linked Commentary: M. Ståhle. J Eur Acad Dermatol Venereol 2020; 34: 1387–1387. https://doi.org/10.1111/jdv.16697 .